Psychosocial impacts of coughing in public places during the COVID-19 pandemic: a cross-sectional study in the western region of Saudi Arabia - Alahmadi, Abdulrahman Dakheel; Mandeeli, Amjed Yunus; Alshamrani, Abdulaziz Mohammed; Alharbi, Mohsen Hani; Ahmed , Mohamed Eldigire; Kumar, Raju Suresh (Medical Journal of Indonesia, 2024)
BACKGROUND Dry cough is a prevalent symptom of COVID-19. During the pandemic, people may mistake this cough for symptoms associated with other respiratory diseases. This increases the risk of individuals with a cough being falsely judged as having COVID-19. This study aimed to investigate the impact of coughing in public places on adults’ mental and social well-being during the COVID-19 pandemic and to explore the role of demographic factors in the relationship between coughing and psychosocial life in public places in the western region of Saudi Arabia. METHODS This cross-sectional study was conducted in the western region of Saudi Arabia, targeting healthy adults aged ≥18 years. The participants were randomly selected using a cluster sampling technique. Data were collected through a self-administered validated questionnaire to explore the psychosocial impact of coughing in public places during the COVID-19 pandemic. Additionally, the questionnaire collected demographic information, smoking habits, cough frequency, consumption of cough medications, history of mild respiratory diseases, and family history of chronic respiratory illnesses. The mean and standard deviation were used to calculate continuous variables, and frequency and percentages were used to present categorical variables. We analyzed the relationships between study variables using the analysis of variance test. RESULTS 288 adults participated in the study, with a 67.2% agreement score. 82.0% of the participants avoided people who coughed in public, while 51.8% felt angry and frustrated when someone coughed in public during the pandemic. CONCLUSIONS COVID-19 has changed how people react to coughing in public. Mild coughs can be mistaken for COVID-19, leading to avoidance.